Public policy and future mineral supplies. (August 2018) - Tilton, John E.; Crowson, Phillip C.F.; DeYoung, John H.; Eggert, Roderick G.; Ericsson, Magnus; Guzmán, Juan Ignacio; Humphreys, David; Lagos, Gustavo; Maxwell, Philip; Radetzki, Marian; Singer, Donald A.; Wellmer, Friedrich-W.
Abstract: A widespread and pessimistic view of the availability of mineral commodities calls for strong government initiatives to ensure adequate future supplies. This article provides a more market oriented and optimistic perspective, one that focuses on production costs and prices rather than physical availability. It sees short-run shortages continuing to plague commodity markets in the future as in the past. Though painful while they last, these shortages are temporary and do not pose a serious long-run threat to human welfare. Moreover, even without government intervention, they self-correct. The sharply higher prices that they evoke create strong incentives that foster supply and curb demand. Potentially more serious are long-run shortages due to mineral depletion. Such shortages are often thought to be inevitable, a conclusion that flows directly from the physical view of depletion. For various reasons, we reject this view of depletion in favor of an economic view. The latter recognizes that depletion may create long-run shortages, but stresses that this need not be the case if new technology can continue to offset the cost-increasing effects of depletion in the future as it has in the past. The economic view also suggests that a list of mineral commodities most threatened by depletion can best be compiled using cumulative availability curves rather than the more common practice of calculating commodity life expectancies based on estimates of available stocks. Highlights: Strong government intervention to mitigate future mineral shortages is unnecessary. Costs and prices are better measures of mineral availability than physical quantities. Short-run shortages occur frequently for many reasons. Long-run shortages due to depletion are extremely rare. Public policy should rely on markets (price signals) and correct their imperfections. Cumulative availability curves can help identify commodities threatened by depletion.